Examining a theoretical concept – (Im)Mobility as a factor of perforation in a rural Hungarian context - Alpek, Levente B.; Tésits, Róbert; Trócsányi, András; Máté, Éva; Németh, Ádám (Geographica Pannonica, 2022)
Rural restructuring became a frame definition to describe the changing circumstances of rurality within modernization and post-modernization processes. When it comes to modernization, differentiation mostly denotes an increasing urban lifestyle, higher level of mobility and flexibility and dynamic society of the rural. However, a brief overview on rural spaces proved, that in many cases the new challenges of modernization or post-modern values indicate a fragmentation in societies. The approach to reach a higher level of mobility due to the centralized spatial structure of workplaces results in a distinction between social groups; what is more, demographic decline intensifies because of the relatively high mobility of certain rural groups. This paper focuses on those social groups, which have a relatively low level of mobility, therefore they get isolated in a rural locality. The settlements, where most of the local society lacks mobility, could cause the perforation of the settlement system, thus the isolation of some rural social groups leads to a dysfunctional settlement structure. In these terms, perforation means a process, in which a settlement loses connections with local centres or other communities due to the low mobility of residents. Therefore, perforation refers to the lack of local networks, an immobile society, and a set of problems, like unemployment, deprivation, or deviant behaviour. According to the author’s presumptions, the mobility of residents could express the volume of perforation as the more isolated the residents are, the less network functions in a rural settlement system can be found. For this reason, this research measures the mobility level of residents in a Hungarian rural locality named Baranyai-Hegyhát, located in the Southern-Transdanubia Region. According to survey data, a mathematical model can describe mobility patterns in this area, which is used as a method to find isolating settlements in a disabled space. The theoretical concept of perforation is supposed to be an experimental approach to interpret complex isolation processes in rural spaces, as such, in this paper, we are to test our theory with the method of the Corrected Mobility Index.
Keywords: post-socialist rurality; rural restructuring; perforation of settlement structure; mobility; labour market; Hungary